IMPLEMENTASI PERATURAN PRESIDEN NOMOR 99 TAHUN 2020 TENTANG PENGADAAN DAN PELAKSANAAN VAKSINASI COVID-19 DI KECAMATAN LINTAU BUO - Silvia Sukma Sari; Nora Eka Putri (SOSIOEDUKASI, 2022)
The government has determined the Corona Virus outbreak as a national disaster as stated in Presidential Decree No. 12 of 2020, which was set on April 13, 2020. With the number of cases of the population affected by Covid-19 increasing every day, causing the death toll. Therefore, the government issued a policy of Presidential Regulation Number 99 of 2020 concerning the Procurement and Implementation of Covid-19 Vaccination, which was set on October 5, 2020. Especially in Lintau Buo Subdistrict, there was an increase in Covid-19 cases, so the Presidential Regulation was implemented in February 2021 in Lintau Buo Subdistrict.. This study aims to examine and determine the extent to which the government and society are trying to succeed in the implementation of Presidential Regulation No. 99 of 2020 in Lintau Buo District. This type of research is a quasi-qualitative research using a simple research method, the withdrawal of informants using a purposive sampling technique. The results of the study indicate that the implementation of Presidential Regulation Number 99 of 2020 in the implementation of stages 1-4 in Lintau Buo District is optimal. This was proven in stage 4, Lintau Buo District achieved the national standard target, namely 75% of the community had been vaccinated and received the predicate of District number 1 in Tanah Datar Regency regarding the achievement of the first stage of vaccination targets.